Evaluation of the efficacy and tolerability of mandelic acid-containing cosmetic formulations for acne skin care - Renata M. Dębowska; Aleksandra Kaszuba; Iwona Michalak; Agata Dzwigałowska; Czanita Cieścińska; Elżbieta Jakimiuk; Joanna Zielińska; Andrzej Kaszuba (Termedia Publishing House, 2015)
Introduction. Acne vulgaris is a common, chronic skin disease that shows a characteristic clinical picture. Skin lesions occur primarily in the seborrheic areas of the body, i.e., the face, back, and chest. Mandelic acid yields very good results when used to treat excessive actinic keratosis (keratosis actinica), hyperpigmentation (lentigo solaris and melasma), and meshlike wrinkles, which are primarily caused by sun-induced aging of the skin. This therapy is well suited for the care of skin with acne vulgaris. Objective. To evaluate the efficacy of dermo-cosmetics containing 5% or 10% mandelic acid for the skin care of patients with acne vulgaris. Material and methods. An open study was carried out on 60 patients with papulo-pustular acne, who applied dermocosmetics to their skin for 2 months. Patients were divided into two subgroups of 30 patients each. One group was tested with a 5% mandelic acid containing cosmetic while the other group was tested with a 10% mandelic acid containing cosmetic. After the treatment was completed, acne severity was evaluated according to the Hellgren-Vincent scale. Results. Physical examinations performed during the study revealed a gradual improvement in the condition of the skin in both groups, with a reduction in the number of pustules, inflammatory nodules, and comedones. The proportion of patients in each group showing a reduction in disease severity according to the Hellgren-Vincent scale was similar. Conclusions. The results of the present study show that products containing 5% or 10% mandelic acid are both safe and effective for the treatment of acne.